PENGARUH KUALITAS PRODUK, INOVASI DAN PERSEPSI HARGA TERHADAP PROSES KEPUTUSAN PEMBELIAN (STUDI PADA KONSUMEN PRODUK TUPPERWARE DI KELURAHAN JINGGOTAN KECAMATAN KEMBANG RW 01 KABUPATEN JEPARA JAWA TENGAH) - Oktavia Sridewinta Yusianti, 13.05.51.0160 (Students' Journal of Economic and Management, 2017)
This study aims to determine and analyze the effect of product quality, innovation and price perceptions of the purchasing decision process in the purchase of Tupperware products in Jepara. This study uses primary data and secondary data with data collection method with questionnaire. Samples taken as many as 100 respondents, using sampling technique in this study using purposive sampling is taking samples with the criteria of consumers who have ever bought Tupperware products in Jepara. Methods of data analysis using multiple linear regression. Test results obtained that the quality of the product has a positive effect on purchasing decisions, innovation has a positive effect on the purchasing decision process and price perception have a positive effect on purchasing decisions. Overall research model is said fit or feasible as research model with coefficient of determination value approaching 1. Keywords: innovation, price perception and purchasing decision process